2023
DOI: 10.1021/acschemneuro.3c00641
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers in Alzheimer’s Disease

Pravat K. Mandal,
Joseph C. Maroon,
Arun Garg
et al.

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disorder that affects millions of people worldwide. The characteristic pathological manifestation of AD includes the deposition of extracellular insoluble β amyloid plaques and intracellular neurofibrillary tangles formed from hyperphosphorylated tau protein. Cost effective and minimally invasive peripheral blood-based biomarkers are critical for early AD diagnosis. Currently, the plasma based two fraction of β amyloid peptide ratio (Aβ42/40) and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A transgenic AD mice model study also showed that GSH depletion precedes amyloid plaque formation [13]. Significant depletion of plasma GSH from mild cognitive impairment (MCI) subjects has also been reported in a longitudinal study [14,15]. This supplemental issue of the Journal of Alzheimer's Disease highlights OS-based AD research from various laboratories around the globe.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…A transgenic AD mice model study also showed that GSH depletion precedes amyloid plaque formation [13]. Significant depletion of plasma GSH from mild cognitive impairment (MCI) subjects has also been reported in a longitudinal study [14,15]. This supplemental issue of the Journal of Alzheimer's Disease highlights OS-based AD research from various laboratories around the globe.…”
mentioning
confidence: 86%
“…Deferiprone) in randomized clinical trials (RCT) involving Prodromal and mild AD patients for cognitive preservation is awaited. The efficacy of the RCT can be monitored from the analysis of plasma GSH and serum iron levels from the trial participants [14]. These valuable data can be kept in a dedicated database called SWADESH [29].…”
mentioning
confidence: 99%
“…Growing evidence suggests that enhancing Aβ peptide clearance contributes to preventing AD. 59,60 In a study by Gao et al , the molecular mechanisms of CGA were explored using a model of Aβ25–35-induced APP/PS1 transgenic mice with SH-SY5Y neuronal damage and cognitive impairment. The findings indicate that CGA significantly enhances spatial memory in APP/PS1 mice, mitigates neuronal damage, inhibits autophagy, and, by activating the mTOR/TFEB signaling pathway, restores brain autophagic flux in APP/PS1 mice, thereby alleviating cognitive impairment.…”
Section: Biological Activities Of Cgamentioning
confidence: 99%
“…Biomarkers analyzed on blood sample are desirable as easily accessible and non-invasive tools. Plasma biomarkers are promising candidates for the early diagnosis of AD, tied to the biological β Amyloid (A) deposition, pathologic Tau (T), and Neurodegeneration (N) [ATN] framework ( 4 , 6 8 ). Recently, plasma glial fibrillary acidic protein (GFAP), an intermediate filament protein of astrocytes, has been demonstrated to be associated with brain amyloid status and the development of clinical AD and cognitive decline ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%